UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DILIHAT DARI PASAL 18 B AYAT 2 UUD 1945 - Hanif Nurcholis (Masalah-Masalah Hukum, 2014)
The status of Village has still been outside of the government bureucratic-system. It is still being positioned as a community that regulated by State and given the governmental tasks. The Law Number 6/ 2014 regarding The Village not includes it into the local government system. This research was conducted in Wilalung Village. The aim of it was to evaluate whether or not the Village in practice has been currently relevant with Article 18 B Verse (2) of Constitution 1945. The Data were collected through several ways: field observation, in-depth interview, focus group discussion, and literature study. This study found that regulation of Village is on the out side bases of the Article 18 B Verse (2).Therefore, the Village-Administration needs to be restructured and into the local government system.